Associations between parental perceptions of neighbourhood environments and active travel to school: IPEN Adolescent study - Timperio, Anna; Duncan, Scott; Akram, Muhammad; Molina-García, Javier; Van Dyck, Delfien; Barnett, Anthony; Salonna, Ferdinand; Rm, Anjana; Sallis, James F; Vorlíček, Michal; Hinckson, Erica; Cain, Kelli L; et al. (The international journal of behavioral nutrition and physical activity, 2025)
BACKGROUND: Studies of correlates of active transport to and from school (ATS) focus mainly on children, have a limited conceptualisation of ATS trips, lack heterogeneity in built environments, and rarely consider effect modifiers. This study aimed to estimate associations of parent-perceived neighbourhood environment characteristics with self-reported ATS among adolescents from 14 countries, and whether associations differ by sex, city/region, and distance to school. METHODS: Observational cross-sectional design. Data were from the International Physical activity and Environment Network (IPEN) Adolescent study and included 6302 adolescents (mean age 14.5 ± 1.7 years, 54% girls) and a caretaker from 16 diverse sites. Adolescents self-reported usual travel to and from school by walking and bicycling (days/week) and time it would take to walk. Parents completed the Neighbourhood Environment Walkability Scale for Youth (13 scores computed). Generalised additive mixed models estimated associations of parent neighbourhood perceptions with 1) any active transport to/from school, 2) regular walking (5-10 times/week), 3) regular cycling to/from school, and 4) profiles of ATS generated using latent profile analyses. Interactions were also explored. RESULTS: Overall, 58.7% reported any ATS, 39.9% regularly walked, 7.7% regularly cycled, and four profiles of ATS were identified: walk to and from school; walk from school; cycle to and from school; no ATS. Distance to school was negatively associated with all outcomes, though evidence was weak for regular cycling to/from school. Land use mix - diversity was positively related to all ATS outcomes except those related to cycling. Accessibility and walking facilities were associated with higher odds of any ATS, regular walking to/from school, and the profile walking to and from school. Residential density was negatively related to regular cycling to/from school. Positive associations were observed between traffic safety and any ATS, and between safety from crime, aesthetics, and odds of regular cycling to/from school. Distance to school, adolescent sex, and city moderated several associations. CONCLUSIONS: Parent perceptions of compact, mixed-use development, walking facilities, and both traffic and crime-related safety were important supportive correlates of a range of ATS outcomes among adolescents in high- and low-middle-income countries. Policies that achieve these attributes should be prioritised to support more widespread ATS.
Keywords: Neighborhood Characteristics; Cross-Sectional Studies; Male; percepce; Walking; Parents; Adolescent; Perception; Correlates; Transportation; Active transport; mužské pohlaví; Cycling; doprava; Exercise; mladiství; chůze; Residence Characteristics; cyklistika; Schools; rodiče; školy; lidé; Physical activity; Environment Design; ženské pohlaví; Walkability; charakteristiky okolí bydliště; Humans; International; Youth; Perceived environment; School travel; průřezové studie; Bicycling; Built Environment; vytvořené prostředí; Female; cvičení; životní prostředí - projekt; charakteristiky bydlení